Gender-Based Labour Force Participation and Wage Gap in Pakistan: Does Globalization Matter. - Sana, Moniba; Jaffri, Atif Ali (JISR management and social sciences & economics, 2021)
This study has investigated the impact of globalisation on gender-based gaps in the labor market (GBGLM) of Pakistan for the period 1982-2017. Particularly, the study has estimated the impact of trade openness(OPEN), foreign direct investment (FDI), workers’ remittance inflows(WRI) and exchange rate(ER) on gender-based labour force participation rate differential (LFPRD) and wage differential (WD). The study has applied the Autoregressive Distributed Lag (ARDL) model and Johansen’s cointegration approach on two models estimated for LFPRD and WD. The error correction models (ECM) have confirmed an error correction mechanism as reflected by negative and significant coefficients of lagged ECM terms. The study has applied all relevant diagnostic tests to ensure the validity of empirical findings. The results of the study indicated that in the long run, OPEN reduced LFPRD and WD, whereas, FDI augmented LFPRD. ER depreciation decreased LFPRD and augmented WD. WRI also augmented LFPRD and WD. The study concluded that OPEN and Real GDP are prominent factors in reducing WD and LFPRD of Pakistan, whereas, FDI and WRI augmented LFPRD. This is a very important finding in the context of the stagnant real sector of Pakistan where agriculture and industry have performed lower than rapidly growing services sector of Pakistan. Since most of the exports emanate from the real sector of Pakistan, therefore, relatively more focus on real sector as compared to financial inflows can play a crucial role in reducing GBGLM of Pakistan. The policy implication based on results is that to reduce GBGLM of Pakistan, trade liberalisation with special focus on the commodity-producing sector is right policy option in Pakistan